Assessing the Potential of Incentive Based Plantation Involving People's Participation - Sinha, Bhaskar; Jha, Shashidhar K.; Khare, Anil Kumar (Indian Forester, 2015)
To encouragemore forestry projects under CDM and other incentive based mechanism, a pilot study was undertaken at household level in Ratlam district of Madhya Pradesh, India, which has a large area of agriculturally unproductive and degraded land. A total of 50 farmers were randomly chosen to know their perceptions and preference in order to take up plantation on modalities of CDM A R projects. The survey showed that majority of farmers expressed their willingness to raise plantation on private land on the basis of co-operative model. The study concluded that Ratlam district has the potential for taking up CDM A R projects and also for any other incentive based plantation, as majority of the pre-requisite factors and conditions required for making CDM A R projects can be fulfilled.